Plant growth-promoting effects of a novel Lelliottia sp. JS-SCA-14 and comparative genome analysis - Jeon, Byeong Jun; Park, Jin-Soo; Hong, Sung-Chul; Lee, Eun Ha; Choi, Jaeyoung; Kim, Jeong Do (Frontiers in Plant Science, 2024)
Bacteria associated with plants play crucial roles in promoting plant growth and health by aiding in nutrient acquisition, including phosphorus. This study presents the isolation and genomic characterization of a potentially new bacterial strain, Lelliottia sp. JS-SCA-14, which exhibits significant plant growth-promoting effects through phosphorus solubilization. A comparative phylogenomic analysis of the complete genome of strain JS-SCA-14 and its closely related strains revealed a unique genomic profile, suggesting it could be a novel species. Genomic identity calculations indicated that JS-SCA-14 significantly deviates from strains belonging to closely related genera, such as Buttiauxella, Citrobacter, Enterobacter, Leclercia, and Lelliottia. A biochemical assay comparing JS-SCA-14 and a closely related strain, Lelliottia jeotgali PFL01 T , showed differing patterns in carbon source utilization and enzyme activities. To assess the plant growth-promoting capabilities of strain JS-SCA-14, tests were conducted to evaluate its siderophore-producing and phosphate-solubilizing abilities. Seed germination assays demonstrated an improvement in germination, seedling length, and vigor compared to untreated controls. Notably, the phosphatedissolving strain JS-SCA-14 led to a significant increase of 34.4% in fresh weight and 35.4% in dry weight of tomato plants compared to the negative control. These findings underscore the significant potential of strain JS-SCA-14 in solubilizing phosphate, thereby enhancing phosphorus availability in the rhizosphere and promoting plant growth and development. This study contributes to our understanding of plant-microbe interactions and suggests the potential application of strain JS-SCA-14 as a bioinoculant for sustainable agriculture and plant nutrient management strategies.